Jumlah Bakteri Asam Laktat (BAL) dalam Digesta Usus Halus dan Sekum Ayam Broiler yang Diberi Pakan Ceceran Pabrik Pakan yang Difermentasi - Tri Setyo Widodo; Bambang Sulistiyanto; Cahya Setya Utama (Jurnal Agripet, 2015)
(The amount of lactic acid bacteria in ileal digesta and secal digesta of broiler fed ration containing fermented abandoned feed)ABSTRACT. The study aims to examine the fermented feed quality in vivo against the amount of lactic acid bacteria in ileal and cecum digesta of broilers. The material used were 105 broiler DOC in 48,244,10g body weight. The experiment was conducted in completely randomized design (CRD) with 3 treatments and 6 replications. The treatments were T0 = Commercial Feed, T1 = spills Feed, T2 = fermented spills feed. Parameters measured were amount of lactic acid bacteria in the small intestine and cecum. Amount of lactic acid bacteria in small intestine and cecum were not normally distributed, was analyzed by Kruskal-Wallis test and followed by Mann-Whitney test. The results of study showed that treatments significantly affect (p0.05) the amount of lactic acid bacteria in the ileal digesta. Feeding fermented spills feed significantly increased amount of lactic acid bacteria in ileal digesta. The use of fermented spills feed not affect the amount of lactic acid bacteria in the cecum digesta. It is concluded that feeding fermented spills feed had a positive effect on broiler by increasing the amount of lactic acid bacteria in the ileal digesta